Short-term versus long-term heart rate variability in ischemic cardiomyopathy risk stratification - Voss, Andreas; Schroeder, Rico; Vallverdu, Montserrat; Schulz, Steffen; Cygankiewicz, Iwona; Vázquez, Rafael; Bayés de Luna, Antoni; Caminal, Pere (Frontiers in Physiology, 2013)
In industrialized countries with aging populations, heart failure affects 0.3%-2% of the general population. The investigation of 24h-ECG recordings revealed the potential of nonlinear indices of heart rate variability (HRV) for enhanced risk stratification in patients with ischemic heart failure (IHF). However, long-term analyses are time-consuming, expensive and delay the initial diagnosis. The objective of this study was to investigate whether 30min short-term HRV analysis is sufficient for comparable risk stratification in IHF in comparison to 24h-HRV analysis. From 256 IHF patients (221 at low risk (IHFLR) and 35 at high risk (IHFHR)) a) 24h beat-to-beat time series b) the first 30min segment c) the 30min most stationary day segment and d) the 30min most stationary night segment were investigated. We calculated linear (time and frequency domain) and nonlinear HRV analysis indices. Optimal parameter sets for risk stratification in IHF were determined for 24 hours and for each 30min segment by applying discriminant analysis on significant clinical and non-clinical indices. Long- and short-term HRV indices from frequency domain and particularly from nonlinear dynamics revealed high univariate significances (p